THE EFFECT OF USING FRAYER MODEL ON STUDENTS’VOCABULARY MASTERY (A STUDY AT THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 LEMBAH SORIK MARAPI IN 2020/2021 ACADEMIC YEAR) - Rahma Donni Lubis (JURNAL LINER (Language Intelligence and Educational Research), 2021)
The aims of this research are to know: 1) the extent of the application of frayer model on students’vocabulary mastery, 2) the extent of the students’ vocabulary mastery before and after taught by using frayer model, 3) whether is any significant effect of frayer model on students’ vocabulary mastery at the eighth grade students of SMP Negeri 1 Lembah Sorik Marapi. The population of this research is all of the eighth grade students of SMP Negeri 1 Lembah Sorik Marapi which consist of 85 students. Sample were 28 students which taken by using purposive sampling. The research method that used was experimental method. To collect the data the researcher used observation sheet and testan multiple choice as an instrument. The mean score of the application of frayer model was 3.21 categorized “Very good”. The students' vocabulary mastery before using the Frayer Model was 55.39 and was included in the "Less" category. Meanwhile, the students' vocabulary mastery with the Inner Model Division was 73.64 and was included in the "good" category.The result of data analysis shows that ttest11.74 while ttable2.05. It means that ttest is bigger than ttable. So, the hypothesis was accepted. It means that there is any significant effect of frayer model on students’ vocabulary mastery at the eighth grade studentsof SMP Negeri 1 Lembah Sorik Marapi.